Empowering yourself to better participate in feedback: a new cognitive-behavioural model for medical learners - Bouchard-Lamothe, Diane; Rowe, Jennifer; Boet, Sylvain; Denis-LeBlanc, Manon (Canadian Medical Education Journal, 2022)
Sharing formative feedback is inherent in the supervision process and the acceptance of feedback by learners is an essential step in learning. However, receiving feedback from the supervisor evokes emotions and accepting it is not easy. Several recommendations guide preceptors on how to share feedback with learners and all emphasize the importance of encouraging the learner to actively interact in the feedback process. Although studies point to the positive effect of informing and training learners about feedback, few focus on their responsiveness to feedback. Under the rubric of developing a personal skill to better accept feedback, we propose a new behavioral model, called H.O.S.T., which aims to guide learners to approach feedback with a personal growth mindset associated with the learning position. Specifically, the model presents an interdependent set of attitudes and behaviors that aim to facilitate emotional management and engagement in the feedback process, in order to initiate the reflective process necessary for learning and to enable the acquisition of targeted skills. The acronym H.O.S.T. reminds students of the four essential elements of the behavioral model: humility, openness, shared explicitness and tenacity. Based on the positive psychology movement, each element is defined and justified by known theoretical concepts. In order to better assimilate the components of the model, the use of internal dialogue is adopted to facilitate the training and adoption of behaviors. The essence of the model is discussed in light of the feedback literacy dedicated to learners.